Combined carbohydrate and protein ingestion during Australian rules football matches and training sessions does not reduce fatigue or accelerate recovery throughout a weeklong junior tournament - Lee, N. A.; Fell, J. W.; Pitchford, N. W.; Hall, A. H.; Leveritt, M. D.; Kitic, C. M. (The Journal of Strength and Conditioning Research, 2018)
Australian rules football (ARF) is a physically demanding sport that can induce high levels of fatigue. Fatigue may be intensified during periods where multiple matches are played with limited recovery time. Combined carbohydrate and protein (CHO + PRO) intake during physical activity may provide performance and recovery benefits. The aim of this study was to investigate whether CHO + PRO ingestion during ARF matches and training sessions throughout a tournament would enhance performance or recovery in comparison with CHO-only ingestion. Australian rules football players (n = 21) competing in a 7-day national tournament participated in this randomized and double-blinded study. Beverages containing either CHO (n = 10) or CHO + PRO (n = 11) were provided during matches (day 1, day 4, and day 7) and training sessions (day 2 and day 3). Countermovement jumps (CMJs), ratings of muscle soreness, and autonomic function were assessed throughout the tournament. Gastrointestinal tract (GI) discomfort was measured after matches. Countermovement jump peak velocity increased in the CHO + PRO group (p = 0.01) but not in the CHO group. There were no differences in the other CMJ variables. In both groups, muscle soreness increased from days 0 and 1 to day 2 (p = 0.05) but did not remain elevated. R-R intervals (time elapsed between successive peaks in QRS complexes) increased in both groups from day 1 to day 7 (mean difference = 59.85 ms, p < 0.01). Postmatch GI discomfort was not different (p > 0.05) between groups. When daily dietary protein is adequate (>1.8 g/kg/d), the ingestion of CHO + PRO during matches and training sessions throughout a tournament does not reduce muscle soreness nor have clear benefits for neuromuscular recovery or modulate autonomic function in junior ARF athletes, compared with that of CHO alone.